Memorial acadêmico: percurso da minha vida estudantil, acadêmica e profissional - ALMEIDA, Izailde Viana de (2023)
This work presents the account of my educational process with the aim of sharing a reflection on the meanings of the teaching experience. My progressive professional experience and the corresponding academic training, from my literacy process to academic life, brings an important meaning, both to my fulfillment as a human person. This sense is built by these two dimensions: human and professional. The first resides in the field of meanings that the recording of personal memories is; the second is reflected in the reflection on teaching work, which is done through a dialogue with academic literature on literacy and literacy processes. In this sense, the report is not exhausted in the simple description of the facts of life, but above all in what they can represent for those who seek to fulfill themselves as education professionals who deal with children in the phase of learning to read and write, as well as what can, with them perform.